Toward the rationalization of research on higher education a survey of higher education research in the Philippines - Bernardo, Allan B.I; Sarmiento, Jenny E. (EDUKASYON, 1997)
"A survey of higher education researches form 1975 to 1996 was conducted to study the nature, scope, and purpose of researches on the different aspects of higher education, and to characterize the higher education research environment in the Philippines. The survey was conducted to contextualize recent calls for more research that will generate knowledge which will lead to the improvement of the quality of Philippine higher education.